2012
DOI: 10.1051/0004-6361/201220100
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the heavy elements in HD 140283

Abstract: Context. HD 140283 is a nearby (V = 7.7) subgiant metal-poor star, extensively analysed in the literature. Although many spectra have been obtained for this star, none showed a signal-to-noise (S/N) ratio high enough to enable a very accurate derivation of abundances from weak lines. Aims. The detection of europium proves that the neutron-capture elements in this star originate in the r-process, and not in the s-process, as recently claimed in the literature. Methods. Based on the OSMARCS 1D LTE atmospheric mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The average difference in the present sample is +0.23 dex. The same discrepancy was also found by Siqueira-Mello et al (2012) for HD 140283, and by Johnson (2002), who analyzed the V abundance in 23 metal-poor stars. Johnson suggested that the cause of this discrepancy might be that hyperfine splitting and NLTE effects had been neglected in the computations.…”
Section: Odd-z Elements: Al K and Scsupporting
confidence: 78%
“…The average difference in the present sample is +0.23 dex. The same discrepancy was also found by Siqueira-Mello et al (2012) for HD 140283, and by Johnson (2002), who analyzed the V abundance in 23 metal-poor stars. Johnson suggested that the cause of this discrepancy might be that hyperfine splitting and NLTE effects had been neglected in the computations.…”
Section: Odd-z Elements: Al K and Scsupporting
confidence: 78%
“…Using the Arlandini et al (1999) nuclear network, the s-processonly [Ba/Eu] 1 ratio is [Ba/Eu] = +1.13, while the r-process-only ratio is [Ba/Eu] = −0.69. In general, the europium and barium ratios indicate that HD 140283 has a higher fraction of r-process elements than s-process elements (Lambert & Allende Prieto 2002;Siqueira Mello et al 2012). In Gallagher et al (2010) we set a lower limit for the [Ba/Eu] ratio, [Ba/Eu] > −0.66, as limited quality in the spectrum around the europium 4129 Å line and uncertainties concerning blends around the europium 4205 Å line did not allow us to make a definitive measurement.…”
Section: Introductionmentioning
confidence: 97%
“…Peterson 2011;Roederer 2012;Siqueira Mello et al 2012). By measuring the ratio of a heavy element whose origin is primarily of the rapid (r-) neutron-capture process with another synthesised primarily through the slow (s-) process, it is possible to determine the ratio of r-to s-process in a star.…”
Section: Introductionmentioning
confidence: 99%
“…HD 140283 has been the subject of numerous studies, especially in more recent years where more sophisticated stellar atmosphere models have been used to determine accurate metallicities and α abundances (e.g. Charbonnel & Primas 2005) and to study neutron-capture elements to understand better heavy element nucleosynthesis (Siqueira Mello et al 2012;Gallagher et al 2010;Collet et al 2009). Concerning the fundamental properties of this star, Bond et al (2013) published a refined parallax π = 17.15 + −0.14 mas, an uncertainty one fifth of that determined by the Hipparcos satellite (van Leeuwen 2007, 17.16 ± 0.68 mas), and assuming zero reddening determined an age of 14.5 Gyr.…”
Section: Introductionmentioning
confidence: 99%